The Study of the Self-Development Model in the Context of Structural Security of the Individual Integrity - Ievtushenko, Iryna V.; Kaliuzhna, Yevheniia Ðœ.; Nezhynska, Olena O. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of the study is the theoretical substantiation and testing of the methodological apparatus for determining the possibility of self-improvement and maintaining the level of personal psychological attitudes for social and professional interaction. Background: The individual is perceived in the social environment as complex integrity having specific sets of its own properties and definitions. The implementation of professional standards, the creation of new organizational and psychological mechanisms in society puts forward new requirements for personality. Method: The article presents a model for the formation of a qualitative perception of the possibilities of correcting motives and personality traits, which impact on the social interaction of a person. Results: Analysis of the obtained results allowed to admit the effectiveness of authors’ experimental methodology. The authors show that the structural support for the development of the psychological characteristics of addictive individuals should be based on an understanding of the boundaries of social and professional interaction and the determination of the possibilities for its adjustment. Conclusion: The authors presented a model for the formation of a qualitative perception of the possibilities of correcting motives and personality traits. This, in turn, forms the possibility of defining a complex that contributes to additional social interaction between the components of the social structure.